Living Zen - Linssen, Robert (Grove Press, 1960)
Living Zen is that rare achievement, both a survey of the rich history of Zen Buddhism and a guide to the practice of this most demanding and effortless art of being. Linssen, a distinguished Belgian scholar, offers a sage corrective to the idea that the Zen way is available only to those prepared to sit life out under the Bhodi-Tree. Gently but insistently he undermines this typically Western view, inviting and enabling us, as Christmas Humphreys puts it in his preface, to take “the leap from thought to No-thought, from the ultimate duality of Illusion/Reality to a burst of laughter and a cup of tea.”